Perceptions of Recreation Quality in Hong Kong: 香港人對康體服務的印象 - DEGRAAF, Don; CHAN, Patrick P. C. (Asian Journal of Physical Education & Recreation, 2003)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Due to the developed economics during the last few decades, increasing demand for leisure services in Hong Kong cannot be denied. The main purpose of this study was to understand the perceptions of quality on service providers from the respective participants. Six participating settings (two public, two non-profit and two commercial) were invited to participate in this study. A total of 350 respondents completed the SERQUAL instrument (either English or Chinese). The findings indicated that participants’ perception of the recreation quality (five dimensions - reliability, responsiveness, assurance, empathy and tangibles) in commercial setting was better than public or non-profit organization. It is important for us to identify a number of keys to pursue excellence and meet the changing needs. 隨著過去數十年的經濟發展，香港人對於康體服務的素求亦不斷增加。本研究之主要目的是探討本地參加者對康體服務之印象。總共有六個機構(包括兩個公營、兩個非牟利及兩個商業被邀請參予這研究；總共有三百五十位參加者回應英文或中文版之SERQUAL問卷。研究結果顯示商業機構所提供之康體服務質素的評分較高，研究結果亦加深我們確定追求卓越之服務質素，與時並進之要素。